PENGARUH SISTEM KEARSIPAN TERHADAP EFISIENSI KERJA PADA KANTOR CAMAT AIR HANGAT KABUPATEN KERINCI: PEBI JULIANTO, S.Sos., MM., CHt - Pebi Julianto (LPPM STIA Nusantara Sakti, 2018)
The purpose of this study is 1. To know the effect Against Filing System Work Efficiency In Depati Head VII, 2. To determine the amount of Effect Against Filing System Work Efficiency At Head Office Air Hangat Kerinci. The approach taken in this research is quantitative descriptive, because it systematically describe the facts and characteristics of the object and the subject under study accurately. The respondents in this research consisted of 20 people. This study uses data collection techniques are field research and research library. The results showed that: 1. By Pearson Product Moment Correlation formula in can r = 0.598 based on a questionnaire that was distributed to the respondents 2. By using the formula coefficient of determination obtained 35.760% figure means Effect Against Filing System Work Efficiency At Head Office Air Hangat Kerinci. while the remaining 64.340% is affected by causes or other factors beyond those examined in this study 3. From the hypothesis test obtained by value t = 3.165 and 2.101 t table according to the provisions of hypothesis testing results obtained t count> t table then Ha Ho accepted rejected. That is a significant difference between Against Filing System Work Efficiency At Head Office Air Hangat Kerinci.